2014
DOI: 10.3126/ije.v3i3.11073
|View full text |Cite
|
Sign up to set email alerts
|

Coliform and Vibrio cholerae Analysis of Drinking Water Collected from Cholera Outbreak Region of Bhaktapur Municipality

Abstract: Water borne infections in Nepal, especially in Kathmandu valley is one the major public health problems, causing thousands of deaths every year. Among three cities in the valley, the water borne infection including cholera is most predominant in Bhaktapur district. So the study was carried out to know the microbial drinking water quality in the city and to determine the prevalence of water borne infections in the specified region of the district in 2012. Altogether eighty (two samples from a single site at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…According to the study, the prevalence rate of V. cholerae from water samples of Bhaktapur was 5% [20] and from Kathmandu, the prevalence was 11.11% [21] which were in agreement to the prevalence of the current study. However, the prevalence of V. cholerae was 0.84% in one study from drinking water of Kathmandu [22].…”
Section: Discussionsupporting
confidence: 89%
“…According to the study, the prevalence rate of V. cholerae from water samples of Bhaktapur was 5% [20] and from Kathmandu, the prevalence was 11.11% [21] which were in agreement to the prevalence of the current study. However, the prevalence of V. cholerae was 0.84% in one study from drinking water of Kathmandu [22].…”
Section: Discussionsupporting
confidence: 89%
“…V. cholerae O1 is still frequently isolated from many outbreak regions of Asian countries [ 7 ]. Nepal is still a cholera endemic country where cholera outbreaks occur every year in the major cities including Kathmandu Valley causing significant morbidity and mortality [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unsafe concentrations of metals including arsenic, iron, manganese, and mercury have been reported in other studies [3][4][5][6][7][8]. Numerous studies have reported that bacterial contamination affected over 80% of samples, including water from dug wells, stone spouts, shallow tube wells, deep tube wells, tap water, and bottled water [6,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 92%